Writing Kerouac's bookmovie: cinematic influence and imagery in the modern road novel. Issue 2 (4th May 2017) - Keevil, Tyler
ABSTRACT: This essay adopts a creative-critical approach in looking at the influence of cinema on the modern road novel. It is in agreement with Mills, in her 2006 work titled The Road Story and the Rebel: Moving Through Film, Fiction, and Television, that the road novel can only be understood as part of a wider genre, the road story, which encompass a broader spectrum of mediums, most notably film. Through exploration of classic texts in the genre – Kerouac, Wolfe, et al. – it demonstrates the extent of cinematic influence on the road novel's gestation and development. In particular, the essay examines Kerouac's concept of 'the bookmovie' and seeks to establish just how prescient and prophetic this has become. In so doing, it will posit that the author's own road novel, The Drive, fits the criteria of the 'bookmovie' through its integration of cinematic homage, as well as its deployment of filmic style and technique.